Komparasi Tentang Pembagian Harta Waris Untuk Anak Luar Nikah Dalam Kuh Perdata Dan Kompilasi Hukum Islam - Ipandang Ipandang (FALASIFA : Jurnal Studi Keislaman, 2020)
This paper examines the comparison of the share of inheritance for children with foreign marriage in the Civil law and the compilation of Islamic laws. Basically, any applicable law regarding inheritance has its own provisions or arrangements regarding the boundaries of the Heritage division of Justice. Similarly, in the Civil Law and the compilation of Islamic laws. In both regulations, there are similarities and differences in inheritance provisions for foreign children. But despite the difference, the essence has the same purpose that the two aim to give welfare and justice to a recognized child of marriage.